Plasma-enhanced metamaterials using microwave radiative power transfer. (14th September 2018) - Kim, Hyunjun; Hopwood, Jeffrey
Abstract: Plasmas are created within a metamaterial structure using low pressure argon and xenon gases. The metamaterial creates an effective negative permeability by using 3D arrays of split ring resonators (SRR) fabricated on thin substrates. Microwave energy incident on this material excites one set of SRRs at 1.5 GHz, which breaks-down the low pressure gas and creates a steady-state plasma. Because this plasma effectively short-circuits the SRRs, the negative permeability is lost. Therefore, a second set of SRRs is included within the metamaterial. These SRRs are isolated from the plasma and shown to be immune to plasma interference. We show that this set of isolated SRRs can maintain negative permeability properties at the design frequency of 1.9 GHz, even with plasma present. Having demonstrated negative permeability, the electromagnetic properties and wave transmission of this metamaterial with periodic SRR-sustained xenon and argon plasmas are investigated. The permittivity of plasma is calculated from collisional Langmuir probe measurements of the plasma density. Spatially resolved measurements show that the central region of each SRR-sustained plasma has negative plasma permittivity with measured plasma density in the range of 0.5–1 × 10 11 cm −3 . The spatial average of the plasma density, however, is too low to create negative permittivity throughout the material.